1995
DOI: 10.1203/00006450-199508000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and β-Adrenergic Mechanisms Modify Contractile Responses to Norepinephrine in Ovine Fetal and Newborn Cerebral Arteries

Abstract: Ovine fetal cerebral artcries exhibit an enhanced contractile response to norepinephrine (NH) compared with newborns and adults. It is possible that P-adrenergic receptors and/or nitric oxide (NO), a putative endothelium-dependent relaxing factor, differentially modulate cerebrovascular responsiveness to NE as a function of developmcnt. 'l'he present study evaluated the effect of thc P-adrenoceptor antagonist, propranolol, and the NO synthasc inhibitor, N~-nitro-I.-arginine methyl estcr (I,NAME), on the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…A limitation of this model is the potential difficulty in extrapolating results obtained in fetuses to newborns, particularly the influence of the uteroplacental circulation and fetal physiology on the cerebrovascular and systemic responses we observed. However, in support of our results and the fetal sheep model, Wagerle et al (35) showed similar contractile responses to NE in fetal and neonatal ovine cerebral arteries that could be modified by nitric oxide and ␤-adrenergic mechanisms. Another potential limitation of our model is the need to estimate fetal weight to calculate drug dosages.…”
Section: Discussionsupporting
confidence: 79%
“…A limitation of this model is the potential difficulty in extrapolating results obtained in fetuses to newborns, particularly the influence of the uteroplacental circulation and fetal physiology on the cerebrovascular and systemic responses we observed. However, in support of our results and the fetal sheep model, Wagerle et al (35) showed similar contractile responses to NE in fetal and neonatal ovine cerebral arteries that could be modified by nitric oxide and ␤-adrenergic mechanisms. Another potential limitation of our model is the need to estimate fetal weight to calculate drug dosages.…”
Section: Discussionsupporting
confidence: 79%
“…This change involves numerous modifications of vascular reactivity, particularly in the larger arteries which have greater regulatory importance in the cerebral circulation than in other vascular beds [27] and appear to play a greater role in autoregulatory and hypoxic cerebrovascular responses in neonates than adults [28]. Overall, these adjustments in cerebrovascular reactivity between the neonate and the adult appear to involve a generalized decrease in sensitivity to many contractile agonists [3,6,7,10,16]. Conversely, cerebrovascular reactivity to a broad variety of vasodilator stimuli appears to increase with age [2,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cerebrovascular reactivity during the perinatal period is a critical determinant not only of cardiovascular homeostasis in the brain, but also of vulnerability to a broad variety of insults. Although it is well established that cerebrovascular reactivity is dramatically different in the immature and mature cerebral circulation [3,[6][7][8][9][10], the mechanistic basis for these differences remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It may be hypothesised that the preterm human brain is placed at risk in two ways. Firstly, inhibition of cerebral arterial vasoconstriction may not be well developed before term [74]; this may explain why damage is seen only in the immature brain. Secondly, the shorter distributor arteries needed by the animal brain because of its relatively smaller size compared to the human brain may explain why even immature animals exposed to simple hyperventilation do not develop evidence of brain damage.…”
Section: Possible Reasons For the Apparent Specific Vulnerability Of mentioning
confidence: 99%